Seasonal variation of selected performance parameters in épée fencers. Issue 3 (September 1993) - Koutedakis, Y; Ridgeon, A; Sharp, N C; Boreham, C
Abstract : In this study, anthropometric measurements were carried out on seven British international male épée fencers, using a maximal treadmill running test, a 20-s Wingate-type test, and isokinetic dynamometry. Testing was conducted on two occasions, 5 to 6 months apart, during mid-off-season (preparation) and mid-in-season (competition) periods. Maximal oxygen intake (VO2max) and maximal respiratory exchange ratio (Rmax) were among the parameters obtained from the treadmill test, while peak and mean anaerobic power outputs were measured during a 20-s maximal effort. Knee extensor and flexor muscle forces from both dominant (leading) and non-dominant (trailing) legs were assessed at 1.04, 3.14 and 4.19 rad sec-1. Statistical analyses revealed lower mean VO2max (P < 0.05) and mean Rmax values (P < 0.02) at the in-season assessments compared with off-season. In-season testing also demonstrated significantly lower peak torques for both dominant and non-dominant knee extensors compared with off-season assessments at all velocities (P < 0.05 to P < 0.004). Furthermore, in-season peak torque for the non-dominant leg flexors was lower (P < 0.03) at 4.19 rad sec-1 than off-season. We conclude that current training practices may account for the observed seasonal variations in performance related physiological parameters in fencers.